2010
DOI: 10.1063/1.3457388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluorine incorporation into HfO2 gate dielectrics on InP and In0.53Ga0.47As metal-oxide-semiconductor field-effect-transistors

Abstract: Articles you may be interested inHigh-performance self-aligned inversion-channel In0.53Ga0.47As metal-oxide-semiconductor field-effecttransistors by in-situ atomic-layer-deposited HfO2Biaxially strained extremely-thin body In0.53Ga0.47As-on-insulator metal-oxide-semiconductor field-effect transistors on Si substrate and physical understanding on their electron mobility HfO2 dielectrics engineering using low power SF6 plasma on InP and In0.53Ga0.47As metal-oxidesemiconductor field-effect-transistors Appl. Phys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…This is likely caused by In-rich IL formation and may explain the recently reported charge instability of InP/ HfO 2 interfaces. 21 In conclusion, we found that ALD Al 2 O 3 provides a high CB offset, of 2.7 eV, with ͑100͒InP. However, it is also observed that the formation of an IL due to oxidation of semiconductor may reduce the barrier height for electrons significantly, particularly if a high electric field is applied ͓cf.…”
mentioning
confidence: 84%
“…This is likely caused by In-rich IL formation and may explain the recently reported charge instability of InP/ HfO 2 interfaces. 21 In conclusion, we found that ALD Al 2 O 3 provides a high CB offset, of 2.7 eV, with ͑100͒InP. However, it is also observed that the formation of an IL due to oxidation of semiconductor may reduce the barrier height for electrons significantly, particularly if a high electric field is applied ͓cf.…”
mentioning
confidence: 84%
“…[1][2][3][4][5] When InGaAs is used, it is grown on an indium phosphide (InP) buffer layer which itself is grown selectively in trenches patterned by a shallow trench isolation process on Si wafers. 6 This InP buffer layer needs to be planarized to remove the overburden and to smoothen the surface.…”
mentioning
confidence: 99%
“…25 Fluorine incorporation into HfO 2 /InP and HfO 2 /In 0.53 Ga 0.47 As gate stacks was reported to improve the drain current and the transconductance and these improvements were attributed to a reduction in the fixed charge and the interface trap density. 26 Passivation of HfO 2 /InP gate stacks by an intermediate Al 2 O 3 layer was observed to enhance the drain current 2.5 times and the transconductance 4 times while reducing the interface trap density. 27 Fluorine treatment of InP/Al 2 O 3 /HfO 2 /TaN gate stacks was found to increase the drain current 100%, the transconductance 50%, and the channel mobility 56%; this enhancement was attributed to a reduction in the gate stack charge.…”
Section: Drain Current Versus Drain Voltage Characteristicmentioning
confidence: 97%